Pelanggaran Hak Merek Yang Telah Terdaftar Berdasarkan Putusan Hakim Nomor 89/PDT.SUS-Merek/2022/PN.Niaga.JKT.PST - Yuliana Indah Sari; Nabilah Farah Dibah; Felly Faradina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
A trademark serves as a distinctive sign identifying the origin of goods or services and is protected under the first-to-file principle, whereby exclusive rights are granted to the first applicant who registers the mark through the Directorate General of Intellectual Property (DGIP). However, disputes may arise when similar trademarks are granted registration despite prior registration by another party. This study aims to analyze the judges' legal considerations in Decision Number 89/Pdt.Sus-Merek/2022/PN Niaga Jkt.Pst concerning trademark infringement and to examine the legal responsibilities of the defendants. The research employed a normative legal method through the analysis of statutory regulations, court decisions, and relevant legal literature. The findings indicate that the court concluded the defendant had acted in bad faith and declared the cancellation of the defendant's trademark registration along with all its legal consequences. Furthermore, the defendants were held responsible for complying with the court's decision and bearing the litigation costs. This study emphasizes the importance of legal certainty and the consistent application of the first-to-file principle to ensure effective protection of registered trademark rights in Indonesia.